Research project on "Systems of traditional education in Malawi” (the continuation: September 1983 to February 1984) by Dr. Gerhard Kubik - Kubik, Gerhard (International Library of African Music, 1987)
Since my first report on the research in Mangochi District July/August 1983 (see: African Music, Vol.VI No.3 pp. 132-137) our team, now comprising four members: Mr Moya Aliya (cultural research student), Mr Donald Kachamba (musician) and Miss Lidiya Malamusi (assistant) besides myself, has been able to continue studies in more districts. These were carried out with permission granted in a letter by the Secretary of the National Research Council, Lilongwe, dated Nov. 16, 1983.
Keywords: Education; African Music; Malawi; Traditional Education